Knowledge on intellectual property as an advantage for scientific research - Zermeño-Guerrero, Jennifer; Garza-Ruiz, Marisela; Rodríguez-Padilla, María Cristina (Unidad Editorial UPTC, 2021)
Abstract The protection of intellectual property represents a key factor for the establishment of the particular rights of the scientific sector, and the clear record of the technological development of a country. The protection strategies of industrial property and copyright are relevant to maintain control of knowledge management, confidentiality during its development and the security of exclusivity in research activities. The relationship between colleagues to present a paper should be trustworthy, however plagiarism is one of the main concerns of researchers when they have to disclose their work where experts in the field are generally present. The objective of this research was to identify the reasons why researchers do not usually protect their scientific works, and through the application of a survey it is described that it is due to the lack of knowledge in the area of protection of intellectual property. It is concluded that it is important to propose the generation of knowledge to researchers about the advantages of implementing a process to protect their works for a relationship of trust with colleagues and students. Keywords: copyright, scientific work, intellectual property, research. JEL Codes: K11 Received: 30/07/2020.  Accepted: 20/02/2021.  Published: 01/06/2021.